IN-VITRO ANTIOXIDANT ACTIVITY AND FREE RADICAL SCAVENGING POTENTIAL OF ROOTS OF RED SAGE - Narayan, Sailesh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of the present work is to study the in-vitro anti-oxidant activities of petroleum ether, ethyl acetate and methanolic extracts of Salvia splendens roots. Methods: The extracts were studied using 1,1-diphenyl-2-picryl hydrazyl, hydrogen peroxide (H2O2), total phenolic content (TPC) and total flavonoid content (TFC). The TPC and TFC were estimated taking gallic acid and rutin calibration curve respectably. Results: All the extracts possess in-vitro anti-oxidant activities. However, the order of possessing activities were methanolic > ethyl acetate > petroleum ether extracts of S. splendens roots. The TPC and TFC was highest in methanolic extract. Conclusion: It can be concluded that S. splendens roots extracts possess anti-oxidant activities. The methanolic extract of S. splendens roots possess highest anti-oxidant activity in-vitro. Keywords: Salvia splendens, In-vitro anti-oxidant, 1,1-diphenyl-2-picryl hydrazyl, Ferric reducing power activity, Hydrogen peroxide scavanging, Total phenolic content, Total flavonoid content Â 